Examining the Transmission Capacity Limits under Steady State Stability Criteria in the Operation of Electricity Market - La, Van Ut; Truong, Ngoc Minh; Nguyen, Manh Cuong (Old Journal, 2017)
The development of Electricity Market (EM) has shaped different market models, including the variety of management and transaction methods. The target of EM is to ensure the transparency, competition of market participants, while maintaining high operational reliability for the power system. The more abundant the transaction models, the more complicated the calculating to maintain the safety operation of power system, especially in the EM with flourishing bilateral trading contracts. This is due to the fact that the more bilateral transmission, the more difficult it is to monitor transmission capacity limits, particularly to track the power transmission limits under steady state stability criteria. For this kind of criteria, the current calculation methods are very limited, and need to be developed. Based on the method proposed in [4], this paper studies algorithms and application programs to quickly calculated and examine the bus transmission capacity limit and bilateral transmission capacity limit under the stability criteria. Example calculation is carried out for the Ward-Hale 6 bus and IEEE 39 bus system.